2017
DOI: 10.1108/ijlm-05-2016-0134
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability-related risk management in buying logistics services

Abstract: Purpose Sustainability-related risk management of logistics service providers (LSPs) is an essential part of sustainability performance of focal companies, as logistics services touch the entire supply chain (SC) – from raw material sources to end-customers. The purpose of this paper, draws on resource-based view and stakeholder theory in exploring how companies can manage environmental and social sustainability-related risks from logistics service suppliers. This kind of capability is essential in order to ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 42 publications
(100 reference statements)
0
36
2
Order By: Relevance
“…Another significant result and with similar strength to the previous hypothesis was the H6, which represents the effect that Logistics has on the Performance of the SME. These findings inform us that these types of companies are obtaining some financial results, but not enough, this may be caused by good practices based on sustainable logistics processes, results that align with the theory of sustainability and empirical studies focused on sustainable and / or green businesses (Hannes, Christian, Christoph, & Michael, 2014;Kalmykova, Sadagopan, & Rosado, 2018;Multaharju et al, 2017). However, we do not find empirical support for H3 and H5, this leads us to infer that open innovation and Environmental CSR directly are not having a significant effect on Performance.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…Another significant result and with similar strength to the previous hypothesis was the H6, which represents the effect that Logistics has on the Performance of the SME. These findings inform us that these types of companies are obtaining some financial results, but not enough, this may be caused by good practices based on sustainable logistics processes, results that align with the theory of sustainability and empirical studies focused on sustainable and / or green businesses (Hannes, Christian, Christoph, & Michael, 2014;Kalmykova, Sadagopan, & Rosado, 2018;Multaharju et al, 2017). However, we do not find empirical support for H3 and H5, this leads us to infer that open innovation and Environmental CSR directly are not having a significant effect on Performance.…”
Section: Discussioncontrasting
confidence: 48%
“…Responsible practices focused on the sustainability of the processes in which logistics intervene under the ecological practices of business have achieved a great amount of organizational and financial benefits. Some authors in their recent research have concluded that environmental social responsibility in conjunction with sustainable logistics has allowed to improve products, improve the quality of the service that the client receives, has reduced waste in the processes and has managed to take care of its resources such as electricity and water, thereby reducing its costs and increasing its economic profitability Jayanti & Rajeev Gowda, 2014;Multaharju et al, 2017). From the theoretical and empirical review, we emit the following hypothesis: H4.…”
Section: Environmental Corporate Social Responsibility Its Relationsmentioning
confidence: 97%
See 1 more Smart Citation
“…An ongoing trend within sustainability logistics is to widen the scope from a traditional company internal focus to include upstream and/or downstream actors (see e.g., [51][52][53]). In line with this, the scope in measuring has also broaden [54,55].…”
Section: Roles and Perspectives Of The Actors Involvedmentioning
confidence: 99%
“…Teuscher, Grüninger, and Ferdinand [136] and Walker [95] affirmed that proactivity in sustainable supply chain management may help manage reputational risk in a company. Multaharju, Lintukangas, Hallikas, and Kähkönen [137] and Kopnina and Blewitt [34] explored how companies can manage sustainability-related risks from the supply chain, an essential process for maintaining their reputation. They argue that suppliers' non-sustainable actions and neglect of sustainability along the supply chain can cause reputational damage and broad financial losses for a focal company.…”
Section: Supply Chain and Reputationmentioning
confidence: 99%